The Intervening Effects of the Organizational Climate of the Provincial Government of Cagayan to the Employees’ Job Performance - Pajarillo Agustin, DPA, Chona (International Journal of Psychosocial Rehabilitation, 2020)
An organization is a system of relating resources that make possible the accomplishment of specific objectives. In public administration, objectives are statements of what an agency or office is officially expected to perform. This aim bends the organizational operation to their accomplishment thus providing the motive for organizational climate. Climate is unseen but undeniably is always present and felt by all who comprise the entire organization. The desire to be accepted and remain part of the organization is inherent in every human being. This undertaking was made to ascertain the present organizational climate of local government units (LGU) of the province of Cagayan and its implication to job performance. Regular employees and administrators of the province were used to provide the needed data. A descriptive correlational design was utilized. Utilizing the data gathered from respondents, results show that the local government units employees and administrators’ performance is very satisfactory which is in consonance to the organizational climate of very much which is very equivalent to a pleasant working atmosphere. This study proves that the organizational climate was very good along the different dimensions and results further revealed that when the administrators are grouped according to personal profile, did not sufficiently relate to perception whereas for the employees’ group, all the personal profile variables directly affect their perception. Such differences manifest the inconsistencies in their perception, thus it is strongly recommended that provisions which would warrant an excellent organizational climate must prevail if quality service is to be delivered to the clientele.